Silanising agents promote resin‐composite repair. (9th October 2015) - Staxrud, Frode; Dahl, Jon E.
Abstract : Objective: The aim of this study was to investigate the effect of silane in the repair of old and new resin‐composite restorations. Method: Part 1: repair of old composite was performed on 60 resin‐composite substrates that were 6 years old and were made of six different brands of composite. Three experiments were performed. In the first experiment, the substrates were ground flat and composite was fixed to the surface with bonding agent without silane (i.e. Clearfil Bond SE only, the control). Shear bond strength (SBS) was tested according to ISO/TS 11405 after thermocycling. In the second experiment, the same 60 substrates were ground again and treated with bis‐silane a 2‐part silane mixed shortly before application before applying bonding agent (Clearfil Bond SE plus silane) and repair composite before SBS testing. In the third experiment, the same substrates were ground again and a one‐step bonding product containing silane (Scotchbond Universal bond containing silane) was used for the repair procedure before SBS testing. Part 2: to evaluate the repair of newly made composite restorations, 66 composite substrates were made and stored in water for 2 months. The specimens were divided into three groups and were tested using the same protocols as used to evaluate repair of old composite. Results: Mean SBS (±standard deviation), in MPa, for repair of old composite was 6.2 ± 4.0 (Clearfil Bond SE only, control), 14.8 ± 7.8 (Clearfil Bond SE plus silane) and 15.3 ± 5.6 (Scotchbond Universal bond with silane), whereas for new composite mean SBS was 15.4 ± 8.6 (Clearfil Bond SE only, control), 23.4 ± 8.3 (Clearfil Bond SE with silane) and 23.7 ± 5.8 (Scotchbond Universal containing silane). A significant difference was observed between the control and the test groups with silanising agents, both in Part 1 ( P < 0.001) and in Part 2 ( P < 0.005). Conclusion: Silanising agents increase the bond strength of the resin composite repair.